Female-specific survival advantage from transcatheter aortic valve implantation over surgical aortic valve replacement: Meta-analysis of the gender subgroups of randomised controlled trials including 3758 patients. (1st January 2018) - Panoulas, Vasileios F.; Francis, Darrel P.; Ruparelia, Neil; Malik, Iqbal S.; Chukwuemeka, Andrew; Sen, Sayan; Anderson, Jonathan; Nihoyannopoulos, Petros; Sutaria, Nilesh; Hannan, Edward L.; Samadashvili, Zaza; D'Errigo, Paola; et al.
Abstract: Transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS) is the first area of interventional cardiology where women are treated as often as men. In this analysis of the gender specific results of randomised controlled trials (RCTs) comparing TAVI with surgical aortic valve replacement (SAVR) we aimed to determine whether gender affects the survival comparison between TAVI and SAVR. We identified all RCTs comparing TAVI versus SAVR for severe AS and reporting 1 and/or 2 year survival. Summary odds ratios (ORs) were obtained using a random-effects model. Heterogeneity was assessed using the Q statistic and I 2 . Four RCTs met the criteria, totalling 3758 patients, 1706 women and 2052 men. Amongst females, TAVI recipients had a significantly lower mortality than SAVR recipients, at 1 year (OR 0.68; 95%CI 0.50 to 0.94) and at 2 years (OR 0.74; 95%CI 0.58 to 0.95). Amongst males there was no difference in mortality between TAVI and SAVR, at 1 year (OR 1.09; 95%CI 0.86 to 1.39) or 2 years (OR 1.05; 95%CI 0.85 to 1.3). The difference in treatment effect between genders was significant at both 1 year (pinteraction = 0.02) and 2 years (pinteraction = 0.04). In women TAVI has a 26 to 31% lower mortality odds than SAVR. In men, there is no difference in mortality between TAVI and SAVR.